Singularities of Solutions of Singular Integral Equations - Il'man, V. M.; Kapustyan, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
From the point of view of singularities of differential mappings, we determine the dependence between the dimension of a family of singular equations and the types of singularities of their solutions.